Design and Implementation of the Bachelor with Honors Program at TU Wien - Ulrich Schmid (Journal of the European Honors Council)
This note outlines the Bachelor with Honors (BHons) program of the Faculty of Informatics at TU Wien, the very first honors program shaped according to American standards at an Austrian university. Besides the usual excellence goals of such programs, a main driver for its creation was exposing gifted students to scientific research very early in their academic careers to hopefully prevent them from accepting industry jobs before doing a Ph.D. Main design challenges were broad accessibility for all top students, demanding and fully transparent admission and completion rules, and dealing with severe resource constraints for running the program.  Main implementation challenges were the need to convince other Faculties at TU Wien that the BHons would not jeopardize the existing Bologna-type study programs and to overcome certain reservations against such “elite programs” in general. Substantial efforts eventually convinced the senate of TU Wien to approve the program, which was started in January 2018. Albeit still in the bootstrapping phase, we are happy to say that the program has developed very well so far.